Is Solution-Focused Brief Therapy Evidence-Based? An Update 10 Years Later. Issue 2 (April 2019) - Kim, Johnny; Jordan, Sara Smock; Franklin, Cynthia; Froerer, Adam
Nearly ten years ago, Families in Society published an article (Kim, Smock, Trepper, McCollum, & Franklin, 2010) that discussed the empirical status of solution-focused brief therapy (SFBT) and its progress toward being accepted as an evidence-based intervention in the United States. In the last decade, new growth of experimental design studies using SFBT with diverse populations has occurred. The current article provides an update on the evidence-base of SFBT, showing favorable results on emotional, behavioral, and interpersonal issues. Resources for practitioners on SFBT training are also included.